Sanitasi Tepung Kulit Singkong - Virgananda Ulfa Kharisma; Indah Werdiningsih; Muryoto Muryoto (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
Cassava peel waste which is not handled properly will become breeding sites for bacteria and germs that will cause health problems. To reduce the negative impact, since cassava peel still has enough nutrient content, it can be reprocessed as flour. The purpose of this study is to determine the differences in shelf-life and acceptance of physical properties (color, odor, texture) of cassava peel flour made from four sanitation treatments by using 10 stages of processing. The type of the research was an experiment with post test only design. Data analysis was conducted descriptively and analytically with one way Anova test at ? 0,05. The conclusion of this studyindicates that the averages of physical acceptance of cassava peel flour between treatments P1, P2, P3 and P4 with formulation F1 to F6 are significantly different. In treatment P3, formulations F3, F4 and F5 are those that can replace wheat flour by 20-60 %; and the differences in shelf-life of cassava peel flour between treatments P1, P2, P3 and P4 ae also significant. By using ESS calculation method, the longest shelf-life is treatment P1, i.e.120 days and 18 hours.